The Effect Of Product Knowledge, Perceived Behavior Control, And Personal Norm On Purchase Intention Of Smes’ Recycled Products In Medan - Muhammad Da’i Kuncoro; Beby Karina Fawzeea Sembiring (Publication Division of International Ecsis Association, 2023)
This study aims to determine the effect of Product Knowledge, Perceived Behavior Control, and Personal Norm on Purchase Intention of SME’s Recycled Products in Medan. This research is associative research and the type of data used is quantitative data. The population of this study is the unknown number of SME’s Recycled Products in Medan. The sample in this study amounted to 100 respondents with using accidental technique. Data analysis used Multiple Linear Analysis. The results of this study indicate that simultaneously Product Knowledge, Perceived Behavior Control, and Personal Norm significantly influence Customer Satisfaction Purchase Intention of SME’s Recycled Products in Medan. Partially, Product Knowledge, Perceived Behavior Control, and Personal Norm has a positive and significant effect on Purchase Intention of SME’s Recycled Products in Medan.